Pengaruh Promosi Online, Nilai Pelanggan dan Kemudahan Transaksi Terhadap Keputusan Pembelian Pada Frozen Food Mbak Bakul - Zulfarida, Anisa Luthfiana; Wardana, Muhammad Sulthon; Viero, Alexandro Sakti Del; Yudiantoro, Deny (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2024)
Marketing strategy is important in order to develop a business. In the era of technological development like today there are many ways to market a product. It is known that currently many people in their daily lives use online media or the internet in carrying out their activities, therefore online marketing is something that must be emphasized in business. In addition, with online marketing, businesses can be reached by a wider audience. This study aims to determine the significance of the influence of (1) online promotion on purchasing decisions at Mbak Bakul's Frozen Food business (2) customer value on purchasing decisions for Mbak Bakul's Frozen Food (3) ease of transactions on purchasing decisions for Mbak Bakul's Frozen Food (4) online promotion, customer value, and ease of transactions on purchasing decisions for Mbak Bakul's Frozen Food. This study uses a quantitative approach with an associative research type. The sampling technique used was accidental sampling, with a total of 100 respondents, namely all buyers of Frozen Food Mbak Bakul Kediri. The data collection technique in this study using a Likert scale through distributing questionnaires, which was then analyzed validity test and reliability test, classical assumption test, hypothesis testing, namely t test, f test, and coefficient of determination test, and multiple linear regression test. From this study, the results show that it is known that the variables of online promotion, customer value, and ease of transactions simultaneously or together have a positive and significant effect on purchasing decisions for Mbak Bakul's Frozen Food. Furthermore, the results of the coefficient of determination test show the R Square coefficient value of 0.761, which means that the online promotion variable, customer value, and ease of transaction are able to explain the purchasing decision variable by 76.1%.